Glutathione Promotes Degradation and Metabolism of Residual Fungicides by Inducing UDP-Glycosyltransferase Genes in Tomato - Yu, Gaobo; Chen, Qiusen; Chen, Fengqiong; Liu, Hanlin; Lin, Jiaxin; Chen, Runan; Ren, Chunyuan; Wei, Jinpeng; Zhang, Yuxian; Yang, Fengjun; Sheng, Yunyan (Frontiers in Plant Science, 2022)
Reduced glutathione (GSH) is a key antioxidant and redox buffer, which is crucial for carrying out the detoxification of xenobiotics in plants. In the present study, glutathione could reduce chlorothalonil (CHT) residues in tomato by promoting the expression of UDP-glycosyltransferase (UGT) gene. In plants, UGTs are important catalyzing glycosylation implicated in several biological phenomena, including the timely response to biotic and abiotic stresses via the activation of phytohormones and defense compounds. Given their importance in plant growth and development, genome-wide analyses have been conducted on Arabidopsis and soybean specimens, though not in the tomato, which is a vital vegetable crop. In this study, we identified 143 UGT genes in the tomato that were unevenly distributed on 12 chromosomes and divided into 16 subgroups, and found that a variety of plant hormones and stress response cis-elements were discovered in the promoter region of the SlUGT genes, indicating that the UGT genes were involved in several aspects of the tomato stress response. Transcriptome analysis and results of qRT-PCR showed that most SlUGT genes could be induced by CHT, and the expression of these genes was regulated by glutathione. In addition, we found SlUGT gene scould participate in plant detoxification through interaction with transcription factors. These findings not only further clarify the potential function of the UGT gene family in detoxification of exogenous substances in tomato, but also provide valuable information for the study of functional genomics of tomato in the future.